Perbedaan Pertumbuhan dan Hasil Kacang Faba (Vicia faba L.) karena Faktor Lokasi Tanam dan Populasi Tanaman - Dina Banjarnahor; Novita Ikawati (Universitas Islam Malang, 2023)
Faba bean (Vicia faba L.) is a highland legume having potential for soil conservation. Upscaling faba bean cultivation requires initial inquiry on its growth and yield. In this research, we have investigated faba bean’s growth and yield in different location (high tunnel and open field) under different population density (1, 2, and 3 plants per pot). We found that interaction between location and population has significant effect on number of leaves, shoot fresh weight, shoot root ratio, and pods weight. Location and population independently have significant effect on plant height, root fresh weight, shoot dry weight, and root dry weight. Cultivation in tunnel, be it in narrow and large planting density, has resulted in higher plants, heavier shoot dry matter, yet lighter root dry matter. Meanwhile, growing single seed per pot has resulted in higher plant and heavier root dry matter. This was applicable in both tunnel and open field. We did not find different chlorophyll content among treatments, therefore we concluded that location and population did not influence leave chlorophyll.